QUANTITATIVE ANALYSIS OF LONGITUDINAL CHANGES IN MULTIMODAL IMAGING OF LATE-ONSET RETINAL DEGENERATION. Issue 8 (August 2021) - Vanderford, Elliott K.; De Silva, Tharindu; Noriega, Dominique; Arango, Mike; Cunningham, Denise; Cukras, Catherine A.
Abstract : Purpose: To quantitatively analyze clinically relevant features on longitudinal multimodal imaging of late-onset retinal degeneration to characterize disease progression. Methods: Fundus autofluorescence (FAF), infrared reflectance, and optical coherence tomography imaging of 4 patients with late-onset retinal degeneration were acquired over 3 to 15 years (20 visits total). Corresponding regions of interest were analyzed on FAF (reticular pseudodrusen [RPD], "speckled FAF, " and chorioretinal atrophy) and infrared reflectance (hyporeflective RPD and target RPD) using quantitative measurements, including contour area, distance to fovea, contour overlap, retinal thickness, and texture features. Results: Cross-sectional analysis revealed a moderate correlation (RPD FAF ∩ RPD infrared reflectance = 63%) between contour area across modalities. Quantification of retinal thickness and texture analysis of areas contoured on FAF objectively differentiated the contour types. A longitudinal analysis of aligned images demonstrates that the contoured region of atrophy both encroaches toward the fovea and grows monotonically with a rate of 0.531 mm/year to 1.969 mm/year (square root of area, n = 5 eyes). A retrospective analysis of precursor lesions of atrophy reveals quantifiable progression from RPD to speckled FAF to atrophy. Conclusion: Image analysis of time points before the development of atrophy reveals consistent patterns over time and space in late-onset retinal degeneration that may provide useful outcomes for this and other degenerative retinal diseases. Abstract : Supplemental Digital Content is Available in the Text.Quantitative analysis of longitudinal multimodal imaging in late-onset retinal degeneration reveal changes in retinal thickness and texture metrics in areas that progress from reticular pseudodrusen to atrophy. An analysis of aligned images demonstrates consistent quantifiable patterns before the development of atrophy that may be useful as outcome measures.